The Predictive Value of Periostin to Diagnose Crohn’s Disease - Keskin, Muharrem; Topkaç, Ali (Turkish Journal of Gastroenterology, 2022)
Background: There is still no sensitive and specific biomarker that can be used in the diagnosis and follow-up of Crohn’s disease, so weaimed to assess the diagnostic accuracy of serum periostin levels in Crohn’s disease.Methods: The study included 40 Crohn’s disease patients aged 18-70 years and considered in remission (Crohn’s Disease Activity Index< 150) at admission. Forty healthy volunteers were included in the study as the control group. Crohn’s patients were divided into 3 maingroups as <4 years, 4-8 years, and >8 years according to the follow-up period (in the group <4 years, it was subdivided into <2 and2-4 years). Serum periostin levels were studied by enzyme-linked immunosorbent assay.Results: Forty Crohn’s disease patients and 40 control participants were included in the study. In the Crohn’s disease group, serumperiostin level was 36.55 ng/mL, while it was 21 ng/mL in the control group, P < .001. Periostin levels in the Crohn’s disease group werehigher in the groups with disease duration <4 years, 4-8 years, and >8 years compared to the control group (P < .001, P < .001, P =.038, respectively). For the diagnosis of Crohn’s disease independent of disease duration, the cut-off periostin level was determined as27.8 ng/mL, while the sensitivity and specificity for this value were 72.5% and 77.5%, respectively.Conclusion: Serum periostin levels of the patients followed up with the diagnosis of Crohn’s disease in remission were found to be significantly higher than the healthy individuals, and cut-off values of serum periostin were obtained to both diagnose Crohn’s disease andpredict the course of the disease.